Visual simulation of access to buildings and public facilities for people with disabilities (PWD) / Zuraihana Ahmad Zawawi ... [et al.] - Ahmad Zawawi, Zuraihana; Khalid, Mohd Khazli Aswad; Zahari, Nurul Fadzila; Hashim, Hasnan; Abdullah Saleh, Alia; Sudirman, Mohd Dzulkarnaen (2022)
This innovation project was created to facilitate teaching and learning for students of Building Surveying programme in UiTM especially for the Building Control and Building Design courses. This project was made to make it easier for students to understand more about the requirements of facilities for people with disabilities (PWD) in the building rather than by just imagining it. There are legal provisions of facilities for people with disabilities (PWD) requirements as stated in Persons With Disabilities Act 2008, Uniform Building By-Laws 1984 (By-law 34A), Building Ordinance 1994 (and By-Laws) of Sarawak (By-law 110A) and MS 1184:2014 (Universal Design and Accessibility in the Built Environment – Code of Practice). A building which is equipped with access and public facilities for PWDs can be achieved if they are included in the design from an early stage. This will also benefit other members of the community, including the elderly.